Serum-Glutamic-Pyruvic-Transaminase (SGPT) and Serum- Glutamic-Oxaloacetic-Transaminase (SGOT) Estimation in Different Groups of Women Infected with Toxoplasmosis - H. AL-Duliamy, Sabreen; N. AL-Qadhi , Ban (Iraqi Journal of Science, 2023)
The aim of this study was to investigate the disturbances of some liver enzymes like GPT and GOT level in different groups of women infected with toxoplasmosis. This study was performed on 600 apparently healthy women (pregnant, miscarriage and single) collected from different hospitals in Baghdad, AL-Yarmouk Teaching Hospital and Fatima AL-Zahra Hospital for Obstetric and children and Hay Hiteen clinic during November 2013 till April 2014. The detection of toxoplasmosis was done by a preliminary screening test LAT and the positive percentage was (29.55%), (30.36%) and (40.08%) for pregnant, miscarriage and single women respectively. While, the confirmation of positive results of LAT was done by ELISA-IgG and the results were (40%), (41.81%) and (18.19%) respectively. The disturbances of GPT and GOT liver function enzymes in those women were evaluated and the result showed that only miscarriage women revealed high significant increase of GPT in comparison to all groups while there was no disturbances of GOT happened in any group of women infected with toxoplasmosis.